Bacteriology Quality of Refill Drinking Water in Some Part of Makassar City - Syamsul, Muharti; Nur, Nur Hamdani; Mat, Mario Aleksius (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Refillable drinking water is one of the most frequently consumed beverages. The quality of drinking water is one of the main requirements for health. Based on data from the Ministry of Health of the Republic of Indonesia 2020, as many as 6,221 samples were examined, only 4,401 drinking water facilities met the requirements for proper water in 2019. The impact of the quality of refilled drinking water that does not meet biological requirements is diarrhea caused by Coliform bacteria. A coliform is a group of bacteria that are contained in large quantities in human and animal feces, so these bacteria are often used as indicators of food and water quality. Contamination of refill drinking water can be caused by raw water sources, production equipment depot sanitation, canteen sanitation, and depot staff personal hygiene. This study aims to determine the bacteriological quality of refill drinking water in the working area of Puskesmas Maccini Sombala Makassar City. This research is a type of quantitative research with descriptive methods. Data collection in research was carried out through observation and interviews. Determination of the research sample using purposive sampling, namely Refill Drinking Water Depot with the most amount of water behavior per day and MPN Coliform examination which was carried out at the Makassar City Health Laboratory Center. Depot with sample code A1 found Coliform bacteria with MPN 4.5 / 10ml in raw water and processed water with MPN 2.0 / 100ml. Whereas samples with A2 and A3 codes were not found Coliform bacteria or MPN 0 / 100ml, both raw water and processed water.